Regional Survey in Lombardy, Northern Italy, on Vascular Surgery Intervention Outcomes During The COVID-19 Pandemic. (April 2021) - Bellosta, Raffaello; Piffaretti, Gabriele; Bonardelli, Stefano; Castelli, Patrizio; Chiesa, Roberto; Frigerio, Dalmazio; Lanza, Gaetano; Pirrelli, Stefano; Rossi, Giovanni; Trimarchi, Santi; Briolini, Franco; et al.
Abstract : Objective: The characteristics and outcomes of patients undergoing vascular surgery hospitalised and managed in Lombardy are described with a comparison of patients tested positive for COVID-19 (CV19-pos) vs . those tested negative (CV19-neg). Methods: This was a multicentre, retrospective, observational cohort study which involved all vascular surgery services in Lombardy, Northern Italy. Data were retrospectively merged into a combined dataset covering the nine weeks of the Italian COVID-19 pandemic phase 1 (8 March 2020 to 3 May 2020). The primary outcome was freedom from in hospital death, secondary outcomes were re-thrombosis rate after peripheral revascularisation, and freedom from post-operative complication. Results: Among 674 patients managed during the outbreak, 659 (97.8%) were included in the final analysis: 121 (18.4%) were CV19-pos. CV19-pos status was associated with a higher rate of complications (OR 4.5; p < .001, 95% CI 2.64 – 7.84), and a higher rate of re-thrombosis after peripheral arterial revascularisation (OR 2.2; p  = .004, 95% CI 1.29 – 3.88). In hospital mortality was higher in CV19-pos patients (24.8% vs . 5.6%; OR 5.4, p < .001;95% CI 2.86 – 8.92). Binary logistic regression analysis identified CV19-pos status (OR 7.6; p < .001, 95% CI 3.75 – 15.28) and age > 80 years (OR 3.2; p  = .001, 95% CI 1.61 – 6.57) to be predictors of in hospital death. Conclusion: In this experience of the vascular surgery group of Lombardy, COVID-19 infection was a marker of poor outcomes in terms of mortality and post-operative complications for patients undergoing vascular surgery treatments.